An audit of patients presenting with clinically benign breast disease to the Helen Joseph Hospital breast imaging unit - Christofides, Nicholas Christopher (My University, 2021)
Background: Benign breast pathology is a common presenting complaintand its assessment is important to characterize so as to not miss malignant pathology. At Helen Joseph Hospital (HJH) patients are triaged at the Breast Clinic according to the clinical suspicion of benign versus malignant disease. The patients are assigned a colourlabel based on their clinical presentation. This triage system affects waiting times between clinical examination and mammography appointments. This study aims to assess the association between clinical examination and the radiological and pathological findings of disorders deemed clinically benign and to ascertain the spectrum of benign breast disorders encountered at HJH. Method: A retrospective study of imaging results of patients at HJH presenting as clinically benign breast disorders from January –June 2018 was conducted. Assessed BIRADS score was noted and if core biopsies were performed, their results and patient demographics were documented. Results: Of the 1263 clinically benign patients presenting from January -June 2018 the radiological assessment was: BIRADS 1: 158 (12.5%), BIRADS 2: 685 (54.2%), BIRADS 3: 292 (23.1%), BIRADS 4a: 54 (4.3%), BIRADS 4b: 29 (2.3 %), BIRADS 4c: 21 (1.7%), BIRADS 5: 24 (1.9%). There were 133 biopsies (including 8 BIRADS 3 patients), with 46 (3.6%) confirmed malignancies. The combined specificity of mammography and ultrasound was 65.52 % (54.56% -75.39%) and combined sensitivity 91.30% (79.21% –97.58%). Conclusion: There is a vast spectrum of benign conditions presenting in this population group with only 3.6% confirmed malignancies, confirming an accurate triage system utilised at the breast clinic. Radiological imaging is highly sensitive but less specific emphasising the triad of clinical, radiological and histological assessment as the gold standard with regard to diagnosis of breast disease.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in Diagnostic Radiology, 2021
Keywords: SDG-3: Good health and well-being; SDG-16: Peace, justice and strong institutions